Biochar residual effects and NPK fertilization on soil chemical properties and yield of rice (Oriyza sativa L.) from third season planting - . Mawardiana; . Sufardi; Edi Husen (Syiah Kuala University, 2013)
The study on the effects of biochar including its residu effect on rice is still limited. This study aimed to determine the effect of biochar residue and NPK fertilization on soil chemical properties and yield of rice (Oryzasativa L.) season three. The experiments were arranged in randomized completely block design with two factors (residual biochar and NPK fertilizer and each treatment was replicated 4 times. Biochar residue consisteds of 2 levels. .i.e. without and with biochar residue(10 tons ha-1). NPK fertilizer consisted of 3 levels that were without and with 135 kg ha-1 and 270 kg NPK ha-1. The overall results showed that the residual biochar in combination with fertilizer significantly affected cation exchange capacity, available P and K, rice growth at 45 and 90 days after planting(DAP), tiller number at 28, 35 and 45 DAP, the number of panicles/ clump, total grain and yield.